TaNAC2, a NAC-type wheat transcription factor conferring enhanced multiple abiotic stress tolerances in Arabidopsis - Mao, Xinguo (Journal of experimental botany, 2012)
Environmental stresses such as drought, salinity, and cold are major factors that significantly limit agricultural productivity. NAC transcription factors play essential roles in response to various abiotic stresses. However, the paucity of wheat NAC members functionally characterized to date does not match the importance of this plant as a world staple crop. Here, the function of TaNAC2 was characterized in Arabidopsis thaliana. A fragment of TaNAC2 was obtained from suppression subtractive cDNA libraries of wheat treated with polyethylene glycol, and its full-length cDNA was obtained by searching a full-length wheat cDNA library. Gene expression profiles indicated that TaNAC2 was involved in response to drought, salt, cold, and abscisic acid treatment. To test its function, transgenic Arabidopsis lines overexpressing TaNAC2-GFP controlled by the cauliflower mosaic virus 35S promoter were generated. Overexpression of TaNAC2 resulted in enhanced tolerances to drought, salt, and freezing stresses in Arabidopsis, which were simultaneously demonstrated by enhanced expression of abiotic stress-response genes and several physiological indices. Therefore, TaNAC2 has potential for utilization in transgenic breeding to improve abiotic stress tolerances in crops